The new puzzle about the treatment of type 2 diabetes after the ACCORD and Da Qing studies - Pfeiffer, Michael; Bauer, Rüdiger von; Nawroth, Peter Paul (Langenbeck's archives of surgery, 2011)
INTRODUCTION: There is a dramatic increase in the worldwide incidence of obesity, diabetes mellitus type 2, and other cardiovascular risk factors, summarized previously under the term "metabolic syndrome". Although preventive lifestyle modifications are effective, they are hard to implement and are therefore associated with a high number needed to treat. In most cases, intervention studies with hard endpoints such as myocardial infarction, stroke, or death are missing. - RESULTS: For example, the Da Qing study proved the efficacy of lifestyle modification with respect to manifestation of diabetes, but failed to show clear benefits regarding cardiovascular mortality. Several studies raised doubt, whether the concept of optimally reducing glucose is the optimal treatment for improving cardiovascular endpoints. Moreover other studies, such as Steno-2, showed an impressive effect of a multimodal therapy on hard endpoints. - CONCLUSIONS: In the future, the focus on new strategies for individualized therapies will increase. Additionally, approaches targeting novel molecular pathways are on the horizon, since plasma levels of posttranslationally modified proteins such as HbA1c are strong cardiovascular risk predictors despite normal glucose levels. For the clinician, it now becomes obvious that epidemiologically proven associations do not necessarily reflect causality. Studies addressing defined clinical endpoints, such as micro- and macrovascular morbidity and mortality are needed, as well as basic research, investigating other pathophysiological mechanisms, e.g., reactive metabolites and the digestive tract. The unexplained reduction in diabetes and its complications by bariatric surgery will give further insight not only into new therapeutic approaches, but also into mechanisms yet to be discovered.